The Works of Marc Chagall in Polish Poetry (from the 1950s to the 1980s) - Szewczyk-Haake, Katarzyna (Porównania, 2021)
The article presents a profound and artistically very successful phenomenon of the reception of Marc Chagall’s works in Polish poetry form the 1950s to the 1980s. Different from the reception of Chagall in other “Western” literatures (examples discussed in the article derive from French poetry), the Polish reception is marked first of all by the events of the Second World War and the Holocaust. As during the war almost all material and cultural traces of the Jewish presence in Poland were annihilated, the works of Chagall became a point of reference for many poets (e.g. Jerzy Ficowski, Joanna Kulmowa, Janusz S. Pasierb, Tadeusz Śliwiak), enabling them to express a part of Polish culture which was tragically deprived of its own forms of expression and existence.